THE FACETS OF GLOBALIZATION IN SOUTH ASIAN ENGLISH FICTION - T. R., Deepak; Naveen. S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The changes are crystal clear in every nook and corner of the human domain with greater emphasis on developments. In the path of development difficulties and challenges have placed the lives of people in jeopardy. With the advent of globalization, individuals are placed in the epicentre to comprehend societal transformations. South Asia is witnessed as the most happening domicile because of its caste, creed, colour, religion, languages and nationalistic strategies in the global scenario. The genres of literature are primarily known for portraying diversified tales in spreading pleasure. But in the global facet, it is an instrument to present the world realistically. It acts as a document to inscribe the dreams, dilemmas, problems and predicaments of the globalized world. The literature of South Asia has shed light on stereotypical issues like violence, insecurity, political turmoil and a dearth of national conscience. Hence, the research harvest embarks on the facets of globalization in South Asian English Fiction with eloquent reference to Amitav Ghosh’s The Shadow Lines (1988) and Ahmed Salman Rushdie’s Midnight’s Children (1981) within the contemporary framework.